A randomized controlled trial of an emotion socialization parenting program and its impact on parenting, children's behavior and parent and child stress cortisol: Tuning in to Toddlers. (February 2022) - Havighurst, Sophie S.; Kehoe, Christiane E.; Harley, Ann E.; Radovini, Alessandra; Thomas, Rae
Abstract: This paper examines the efficacy of a universally-offered parenting program, Tuning in to Toddlers (TOTS), that aims to improve parent emotion socialization, reduce parent and toddler stress and improve social, emotional, and behavioral functioning in toddlers. Three hundred parents of an 18–36 month old toddler were cluster randomized into intervention or control. Parents in the intervention participated in 6 × 2 h group sessions of TOTS. Baseline and 12-months post-intervention measures were collected using parent-report questionnaires and hair samples from parents and toddlers of systemic cortisol stress. Compared to controls, intervention parents reported significantly greater reductions in difficulties in emotion regulation (difficulty remaining goal directed: 95% CI.10, 1.71, p = .028; lack of access to strategies: 95% CI 0.62, 2.42, p = .001), emotion dismissing (beliefs: 95% CI 2.33, 4.82, p < .001; behaviors: 95% CI 0.32, 0.65, p = <.001), greater increase in empathy (95% CI −2.83, −1.50, p < .001), emotion coaching (beliefs: 95% CI −2.56, −0.27, p = .016; behaviors: 95% CI −0.58, −0.24, p = <.001), children's behavior (95% CI 0.19, 2.43, p = .022) and competence (95% CI −1.46, −0.22, p = .008). Significant greater reductions in systemic cortisol were found for intervention but not control children (95% CI 0.01, 0.35, p = .041). Findings provide preliminary support for the use of TOTS as a universal prevention program to improve parent emotion socialization and children's functioning. Trial Registration: Australian and New Zealand Clinical Trials Registry: ACTRN12615000962538. Highlights: Toddlerhood is a time of increased autonomy and heightened emotions that can lead to strong reactions in parents making it an important time for parenting interventions. This cluster randomized controlled trial tested a group program teaching parents helpful ways of responding to children's emotions as well as assisting parents in their own emotion regulation. At 12-month follow-up, parents in the intervention but not the control condition reported improved emotion regulation, more optimal responses to their children's emotions, decreased child behavior problems and improved child competence. At follow-up biological measures showed children in the intervention condition had lowered systemic stress cortisol but children in the control condition did not. Tuning in to Toddlers altered parenting associated with children's emotional, behavioral and neurophysiological functioning, suggesting this universal intervention may be beneficial at this developmental stage.